Biomechanical assessment of upright birthing positions using marker-based and markerless motion capture systems - Lauren Haworth; Inderjeet Kaur; Maimoona Ahmed; Anastasia Topalidou (PLoS ONE, 2025)
Understanding the effects of birthing positions on labour is crucial for optimising maternal and foetal outcomes. Upright positions are encouraged but their biomechanics are not fully understood. Biomechanical changes during labour can make certain positions more or less favourable depending on individual physical characteristics. Understanding these factors is essential for tailoring strategies that enhance maternal comfort and facilitate labour. This study aimed to quantify the biomechanics of seven common upright birthing positions, comparing their biomechanical characteristics and evaluating the sensitivity and accuracy of marker-based and markerless motion capture systems. Fifteen healthy, non-pregnant women performed seven upright birthing positions. Hip, pelvis, and trunk kinematics were assessed using a 9-camera marker-based system and an 8-camera markerless system. Significant biomechanical differences were found between birthing positions. The “squat” position showed the most hip flexion and abduction, “B-Ball” had the greatest anterior pelvic tilt, and “all-fours” exhibited the most posterior tilt. For the trunk, “upright” led to the most extension, and “elbows bent knees” showed the most flexion. Agreement between systems varied by joint and plane: it was moderate to strong for hip angles in the coronal plane and for pelvic angles in the transverse plane, but limited in the sagittal plane and inconsistent for trunk measures. This study highlights the biomechanical differences in upright birthing positions and emphasises the need for personalised birthing strategies. Understanding labour biomechanics is crucial for improving maternal and foetal well-being and reducing complications. By providing comprehensive and evidence-based information, women can make informed decisions about their birthing positions, enhancing outcomes and lowering the risk of maternal and neonatal complications globally.